The Influence of E-Learning and Learning Interests on Learning Outcomes of Physical Education in 11th Students of SMA Negeri 8 Medan - Denny Syahputra Panjaitan; Nurhayati Simatupang; Sanusi Hasibuan; Indrakasih Indrakasih (Budapest International Research and Critics University, 2021)
The purpose of this study was to explain the effect of differences in learning outcomes of physical education through edmodo and google classroom on Class XI students of SMA Negeri 8 Medan. This research method uses an experimental method with a 2x2 level design. The data analysis technique used analysis of variance. The research instrument used a questionnaire. The results of the research that have been carried out state that: (1) Based on the results of the analysis of variance in the list of attachments at the level of α = 0.05, it is obtained that F0 <Ft is 0.279 <4.11. (2) Then in the Tukey test in groups A1B1 and A2B1 where = 1.681 and = 2.95. Research conclusions: 1) There are differences in physical education learning outcomes through edmodo and google classroom.